PENGARUH MEDIA SOSIAL FACEBOOK TERHADAP PERILAKU SOSIAL MASYARAKAT DI DESA DUSUN CURUP KECAMATAN AIR BESI KABUPATEN BENGKULU UTARA - Nely Rohati; Linda Astuti; Bakat Seno Pratomo; Franro Franro (Jurnal Saintifik (Multi Science Journal), 2022)
The purpose of this study was to determine whether or not there was an influence of social media Facebook on the social behavior of the people in Dusun Curup Village, Air Besi District, North Bengkulu Regency. This study uses a quantitative approach, a quantitative approach is an approach that describes a problem so that the results of the study can be generalized. The results of hypothesis testing explain that the t-count value in this study is greater than the t-table, with a comparison of t-count (9.01875) > t-table (1.664). This value states that Ha (the working hypothesis) is accepted and Ho (the hypothesis is rejected). This means that there is a significant influence between Facebook social media users on people's social behavior, but the effect is only 2.67%. Qualitatively, it turns out that statements using social media Facebook are not dominantly able to change aggressive behavior in community life and in the family, because based on the test results the percentage is only 2.67%. This proves that there are other factors in this case, it is suspected that there are other social media that are able to change people's behavior.